2011
DOI: 10.1007/s10916-011-9656-7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Physicians’ Adoption of Healthcare Information Technology: An Empirical Study on Multiple Hospitals

Abstract: Prior research on technology usage had largely overlooked the issue of user resistance or barriers to technology acceptance. Prior research on the Electronic Medical Records had largely focused on technical issues but rarely on managerial issues. Such oversight prevented a better understanding of users' resistance to new technologies and the antecedents of technology rejection. Incorporating the enablers and the inhibitors of technology usage intention, this study explores physicians' reactions towards the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 49 publications
0
60
0
1
Order By: Relevance
“…Therefore, assessing the findings of this research in the light of existing research on the acceptance of HIT, which is very rich, may provide fruitful insights. In early studies, HIT was considered as a threat and an extra workload that is not compensated for by an increase in income (Lin et al, 2012). In the early 2000s, eHealth technologies were discussed in terms of effectiveness, safety, and quality, where the cost-effectiveness of HIT and a lack of best practices were two of the most significant debates (Black et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, assessing the findings of this research in the light of existing research on the acceptance of HIT, which is very rich, may provide fruitful insights. In early studies, HIT was considered as a threat and an extra workload that is not compensated for by an increase in income (Lin et al, 2012). In the early 2000s, eHealth technologies were discussed in terms of effectiveness, safety, and quality, where the cost-effectiveness of HIT and a lack of best practices were two of the most significant debates (Black et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The Technology Acceptance Model has been used to examine physician's adoption of new technologies such as telemedicine, 27 MEDLINE, 26 clinical information systems, 25,31 and electronic medical records. [32][33][34] In at least two prior studies using the Technology Acceptance Model involving physicians, attitude has been shown to explain the greatest amount of variance in physicians' intention to use selected technologies. 25,26 In this study, attitude also explained the greatest amount of variance in EPs' intention to use the PAT database among nonusers.…”
Section: Discussionmentioning
confidence: 99%
“…During this process, decision makers need to carry out critical decisions and coordination for achieving alignment System design and implementation between business and IT. Here, the EMR implementation could change the existing work processes that may introduce barriers to its adoption [13]. A good understanding and knowledge about EMR systems and supporting technologies could drive the clinic director to make commitment to communication and coordination between IT and clinical staff for EMR implementation and to locate required resources for EMR implementation in care processes.…”
Section: Relationship Between Clinic Director's Support For Emr Implementioning
confidence: 99%